Las técnicas grafoplásticas como estrategia didáctica para el desarrollo de la motricidad fina de los niños de nivel inicial ii paralelo a del centro de educación inicial fiscomisional niño Jesús de la ciudad de Loja periodo académico 2018 - 2019. - Jimenez Quezada, Ivonne Sevignne (2020)
The present thesis entitled: THE GRAPHOPLASTIC TECHNIQUES AS DIDACTIC STRATEGY FOR THE DEVELOPMENT OF THE FINE MOTOR OF CHILDREN OF BEGINNER LEVEL II PARALEL A OF FISCO MISIONAL INITIAL EDUCATION CENTER NIÑO JESÚS OF THE CITY OF LOJA ACADEMIC PERIOD 2018-2019. Has as main general objective to determine the influence of the graphoplastic techniques as didactic strategy for the development of the fine motor of children of beginner level II; the used methods were: scientific, inductive, deductive, descriptive and analytic–synthetic ;the techniques and instruments employed: interview applied to a teacher of the institution and the evaluative scale adapted with the skills of the Initial Education Curriculum to assess fine motor applied to 17 kids who constituted the sample researched. The results product of the diagnostic indicates that there is a 88% of fine motor difficulty, therefore determine the imminent presence of a problematic that was attend to the elaboration of the present research it was applied an alternative proposal with activities directed to improve the fine motor and as result of it was showed a notable increase of 94% that acquired those skills, demonstrating that the graphoplastic techniques as didactic strategy influence in the development of the fine motor. Concluding that the guide of activities named “Moving my little hands I have fun” based in graphoplastic techniques such as: vitral, free drawing, stamping, soaked chalk, drag of modelling clay, finger painting, blind drawing and pluviometry allow that the children develop their fine motor.